MANAJEMEN ASUHAN KEBIDANAN BAYI BARU LAHIR NY ‘S’ DENGAN BCB/SMK/SPONTAN DI PUSKESMAS TINGGIMONCONG KABUPATEN GOWA - Sumaifa, Sumaifa; Nurfadila, Nurfadila; Ibrahim, Sitti Hasrah (AHM Center, 2025)
Physiological newborns are babies born with a gestational age of more than or equal to 37 weeks with a weight of 2500 grams to 4000 grams. During birth, many physical and psychological changes begin to occur in the baby's body, therefore careful supervision is needed to determine how to adapt to life outside the womb. Newborns really need immediate, fast, precise, safe and clean care. This is important for newborns Research Objective: The case study is to implement Normal Newborn Midwifery Care for Baby Mrs. S at the Tinggimoncong Health Center in 2024 with the implementation of midwifery care management according to the midwife's authority. Research Method: The method used in this study is descriptive with a case study approach using seven steps of Varney midwifery care management and SOAP progress notes. Results of the case study research have been carried out through the assessment and analysis of data on Midwifery Care for Newborns Mrs.